Measurement and Managing the Revenue Risks of Toll Roads - Alshamleh, Osaid A. A. (Eastern Mediterranean University (EMU) - Doğu Akdeniz Üniversitesi (DAÜ), 2021)
Transportation infrastructure is considered the engine of countries economic development. Traditionally, implementing and financing such a project has been done by governments through the national budgetary funds. Such projects' benefits attracted the private sector to be involved in these projects, reducing the burden on governments, providing better quality measures, and generating a return that compensates the opportunity cost of their capital and the risk involved. This process was done under public-private partnership agreements. The revenue generated by these projects is enormous but also surrounded by immense uncertainties. Specifically, forecasting errors resulted from the long-term revenue and expenditure projections to recover the capital expenditure and yield a satisfactory return to equity owners. The study aims to conduct an integrated investment appraisal that assesses the overall potential of the famous Riviera Marcory toll bridge in Ivory Coast using cost-benefit analysis (CBA) approach. Keywords: Infrastructure, Toll Bridge, Public-Private Partnership, Cost-Benefit Analysis, Ivory Coast.

ÖZ: Ulaştırma altyapısı, ülkelerin ekonomik gelişiminin lokomotifi olarak kabul edildi. Geleneksel olarak, böyle bir projenin uygulanması ve finanse edilmesi hükümetler tarafından ulusal bütçe fonları aracılığıyla yapılırdı. Bu tür projelerin faydaları, özel sektörü bu projelere dahil olmaya çekmiş, böylelikle hükümetler üzerindeki yükü azaltmış, daha kaliteli önlemler sunmuş ve sermayelerinin fırsat maliyetini ve içerdiği riski telafi eden getiri üretmiştir. Bu süreç, kamu özel ortaklık anlaşmaları kapsamında yapıldı. Bu projelerden elde edilen gelir muazzamdır, ancak aynı zamanda büyük belirsizliklerle çevrilidir. Özellikle, uzun vadeli gelir ve harcama projeksiyonlarından kaynaklanan tahmin hataları nedeniyle sermaye harcamalarını geri kazanmanın yanı sıra öz sermaye sahiplerine tatmin edici bir getiri sağladı. Çalışma, maliyet fayda analizi (CBA) yaklaşımını kullanarak Fildişi Sahili'ndeki ünlü Riviera Marcory ücretli köprüsünün genel potansiyelini değerlendiren entegre bir yatırım değerlendirmesi yapmayı amaçlamaktadır. Anahtar Kelimeler: Altyapı, Ücretli Köprü, Kamu Özel Ortaklığı, Fayda Maliyet Analizi, Fildişi Sahili
Master of Science in Banking and Finance. Institute of Graduate Studies and Research. Thesis (M.S.) - Eastern Mediterranean University, Faculty of Business and Economics, Dept. of Banking and Finance, 2021. Supervisor: Assoc. Prof. Dr. Hasan Ulaş Altıok.
Keywords: Banking and Finance; Cost-Benefit Analysis--Riviera Marcory Bridge--Ivory Coast; Revenue--Financial management; Infrastructure; Toll Bridge; Public-Private Partnership; Cost-Benefit Analysis; Ivory Coast